2015
DOI: 10.1038/srep17875
|View full text |Cite
|
Sign up to set email alerts
|

Systematic comparison of variant calling pipelines using gold standard personal exome variants

Abstract: The success of clinical genomics using next generation sequencing (NGS) requires the accurate and consistent identification of personal genome variants. Assorted variant calling methods have been developed, which show low concordance between their calls. Hence, a systematic comparison of the variant callers could give important guidance to NGS-based clinical genomics. Recently, a set of high-confident variant calls for one individual (NA12878) has been published by the Genome in a Bottle (GIAB) consortium, ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
244
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(261 citation statements)
references
References 25 publications
16
244
1
Order By: Relevance
“…Previous reports also showed the reduced sensitivity of Bowtie2 [35,36] while others revealed only minor [38] or inconclusive [40] differences between Bowtie2 and BWA. Interestingly, Li attributes the differences between variants called from BWA and Bowtie2 alignments to lower mapping scores that Bowtie2 assigns to reads with additional suboptimal alignments [36].…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports also showed the reduced sensitivity of Bowtie2 [35,36] while others revealed only minor [38] or inconclusive [40] differences between Bowtie2 and BWA. Interestingly, Li attributes the differences between variants called from BWA and Bowtie2 alignments to lower mapping scores that Bowtie2 assigns to reads with additional suboptimal alignments [36].…”
Section: Discussionmentioning
confidence: 95%
“…For example, a recent study showed that one pipeline produces more than 4-fold more single-nucleotide variants (SNVs) from the same dataset than other pipelines (1). Published studies compared different pipelines that employ open source and commercial software, and most of them analyze NGS data generated by using Illumina's platform (1,15,39). There is no publicly available datasets applicable to WES of clinical samples of cancer tissues collected at single institute, which are sequenced at sufficient depths using the Ion Proton System.…”
Section: Identification Of Somatic Mutations From Wes Datamentioning
confidence: 99%
“…We obtained 0. 27,28 , GATK remains the most adopted variant caller for Illumina data, while the Torrent Variant Caller (TVC) is almost the only one adopted for ION data. Both approaches produce a discrete percentage of false positive calls, as we observed in our datasets as well (Supplementary Table S2).…”
Section: Features Importancementioning
confidence: 99%